Prevalence of Blood Parasites in Local Chickens in Qaradagh District, Sulaimani – Iraq - Abdullah, Shadan Hassan (The Iraqi Journal of Veterinary Medicine, 2013)
Hemosporidians are intracellular protozoan parasites found in blood cells and tissues of their avian hosts. They are worldwide distributed and occur in a variety of avian species, including domestic chicken. Blood parasites among village chickens in Qaradagh district, Sulaimani Province in Kurdistan region Iraq, were surveyed during the period of March-June for the year 2012. Haemoparasites investigation was done by microscopic examination of stained blood films which prepared from 170 local chickens (Gallus domesticus).The overall prevalence of all species of haemosporidian parasites over the studied period in tested individuals was 133 (78.2%) with 114 (85.7%) single and 19 (14.3%) mixed genera infections. Plasmodiumspp. was the most prevalent haemoparasite (52.6%) followed by Haemoproteus spp., (19.5 %) and Leucocytozoon spp. (13.5%).The study has reported high prevalence rate of haemoparasites. There isn't enough information about prevalence of avian blood parasites in the studied area, the present study detect for the first time existent of haemoparasites.